Preparation of polypyrrole nanoparticles in mixed surfactants system - Kwon, Woo June; Suh, Dong Hack; Chin, Byung Doo; Yu, Jae-Woong (WILEY, 2008)
Polypyrrole nanoparticles were prepared by emulsion polymerization, and the surface charge of PPy nanoparticles was controlled by the mixed surfactant system of dodecylbenzene sulfonic acid and isooctylphenyl ether. The shape and size of nanoparticles prepared could be controlled by changing concentration of surfactant. In addition, it was confirmed that the nanoparticles with good conductivity could be obtained by this preparation method. Consequently, well dispersed PPy nanoparticles with 60-100 nm in diameter with cubic shape were obtained and whose conductivity was 56.53 S/cm. (C) 2008 Wiley Periodicals, Inc.
Keywords: POLYMERIZATION; POLYANILINE; CONDUCTIVITY; POLYSTYRENE; FABRICATION; TEMPLATE